Difference between revisions of "Pythagorean triple"
m |
(added general form of Pythagorean triples and proof) |
||
Line 38: | Line 38: | ||
== Primitive Pythagorean Triples == | == Primitive Pythagorean Triples == | ||
A Pythagorean triple is called ''primitive'' if its three members have no common [[divisor]]s, so that they are [[relatively prime]]. All of the above triples are primitive. Integral [[multiple]]s of the above triples will also satisfy <math>a^2 + b^2 = c^2</math>, but they will not form primitive triples. For example, any three numbers in the form of <math>(3x, 4x, 5x)</math>, such as <math>(6, 8, 10)</math>, will also satisfy it. | A Pythagorean triple is called ''primitive'' if its three members have no common [[divisor]]s, so that they are [[relatively prime]]. All of the above triples are primitive. Integral [[multiple]]s of the above triples will also satisfy <math>a^2 + b^2 = c^2</math>, but they will not form primitive triples. For example, any three numbers in the form of <math>(3x, 4x, 5x)</math>, such as <math>(6, 8, 10)</math>, will also satisfy it. | ||
+ | |||
+ | === General Form of Primitive Pythagorean Triples === | ||
+ | |||
+ | '''Theorem.''' A triple of integers is a primitive Pythagorean triple if and only if it may be written in the form <math>(m^2-n^2, 2mn, m^2 + n^2)</math> or <math>(2mn, m^2-n^2, m^2+n^2)</math>, where <math>m > n</math> are relatively prime positive integers of different [[parity]]. | ||
+ | |||
+ | ==== Proof ==== | ||
+ | |||
+ | Let <math>(a,b,c)</math> be a primitive Pythagorean triple. If <math>a</math> and <math>b</math> both odd, then we must have | ||
+ | <cmath> c^2 \equiv a^2 + b^2 \equiv 1+1 \equiv 2 \pmod{4}, </cmath> | ||
+ | which is a contradiction, since 2 is not a [[quadratic residue | square]] [[modulus | mod]] 4. Hence at least one of <math>a</math> and <math>b</math>, say <math>b</math>, is even. Then <math>a</math> must be odd, since <math>a</math> and <math>b</math> must be relatively prime. It follows that <math>c</math> is odd as well. It follows that the numbers <math>s = (c+a)/2</math> and <math>d = (c-a)/2</math> are positive integers. These positive integers must be relatively prime, since any common divisor of <math>s</math> and <math>d</math> must divide both <math>s+d= c</math> and <math>s-d = a</math>. Since <math>a = s-d</math> and <math>c= s+d</math>, it follows that | ||
+ | <cmath> b = \sqrt{c^2 -a^2} = \sqrt{(s+d)^2 - (s-d)^2} = \sqrt{4sd} = 2\sqrt{sd} . </cmath> | ||
+ | Since <math>\sqrt{sd} = b/2</math> must be an integer and <math>s</math> and <math>d</math> are relatively prime, it follows that <math>s</math> and <math>d</math> are perfect squares. Hence we may denote <math>s= m^2</math> and <math>d = n^2</math> for integers <math>m</math> and <math>n</math>. Since <math>m^2 + n^2 = s+d = c</math> is odd, it follows that <math>m^2</math> and <math>n^2</math> must have different parity, so <math>m</math> and <math>n</math> have different parity. Finally, we observe that | ||
+ | <cmath> (m^2-n^2)^2 + (2mn)^2 = m^4 + 2m^2n^2 + n^4 = (m^2+n^2)^2, </cmath> | ||
+ | so any triple of the form specified in the theorem is a Pythagorean triple; it must furthermore be a primitive Pythagorean triple, since any common factor of <math>m^2 - n^2</math> and <math>m^2 + n^2</math> (both of which are odd integers, since <math>m</math> and <math>n</math> have different parity) must also be a factor of both <math>(m^2 + n^2) + (m^2-n^2) = 2m^2</math> and <math>(m^2+n^2) - (m^2 - n^2) = 2n^2</math>, which are integers with no common factor greater than 2. <math>\blacksquare</math> | ||
== See also == | == See also == | ||
* [[Pythagorean Theorem]] | * [[Pythagorean Theorem]] | ||
* [[Diophantine equation]] | * [[Diophantine equation]] |
Revision as of 21:53, 18 December 2007
A Pythagorean triple is a triple of positive integers, such that
. Pythagorean triples arise in geometry as the side-lengths of right triangles.
Contents
Common Pythagorean Triples
These are some common Pythagorean triples:
(3, 4, 5)
(20, 21, 29)
(11, 60, 61)
(13, 84, 85)
(5, 12, 13)
(12, 35, 37)
(16, 63, 65)
(36, 77, 85)
(8, 15, 17)
(9, 40, 41)
(33, 56, 65)
(39, 80, 89)
(7, 24, 25)
(28, 45, 53)
(48, 55, 73)
(65, 72, 97)
Primitive Pythagorean Triples
A Pythagorean triple is called primitive if its three members have no common divisors, so that they are relatively prime. All of the above triples are primitive. Integral multiples of the above triples will also satisfy , but they will not form primitive triples. For example, any three numbers in the form of
, such as
, will also satisfy it.
General Form of Primitive Pythagorean Triples
Theorem. A triple of integers is a primitive Pythagorean triple if and only if it may be written in the form or
, where
are relatively prime positive integers of different parity.
Proof
Let be a primitive Pythagorean triple. If
and
both odd, then we must have
which is a contradiction, since 2 is not a square mod 4. Hence at least one of
and
, say
, is even. Then
must be odd, since
and
must be relatively prime. It follows that
is odd as well. It follows that the numbers
and
are positive integers. These positive integers must be relatively prime, since any common divisor of
and
must divide both
and
. Since
and
, it follows that
Since
must be an integer and
and
are relatively prime, it follows that
and
are perfect squares. Hence we may denote
and
for integers
and
. Since
is odd, it follows that
and
must have different parity, so
and
have different parity. Finally, we observe that
so any triple of the form specified in the theorem is a Pythagorean triple; it must furthermore be a primitive Pythagorean triple, since any common factor of
and
(both of which are odd integers, since
and
have different parity) must also be a factor of both
and
, which are integers with no common factor greater than 2.